Benchmarking membrane protein detergent stability for improving throughput of high-resolution X-ray structures. - Sonoda, Y; Newstead, S; Hu, N; Alguel, Y; Nji, E; Beis, K; Yashiro, S; Lee, C; Leung, J; Cameron, A; Byrne, B; Iwata, S; et al. (2011)
Obtaining well-ordered crystals is a major hurdle to X-ray structure determination of membrane proteins. To facilitate crystal optimization, we investigated the detergent stability of 24 eukaryotic and prokaryotic membrane proteins, predominantly transporters, using a fluorescent-based unfolding assay. We have benchmarked the stability required for crystallization in small micelle detergents, as they are statistically more likely to lead to high-resolution structures. Using this information, we have been able to obtain well-diffracting crystals for a number of sodium and proton-dependent transporters. By including in the analysis seven membrane proteins for which structures are already known, AmtB, GlpG, Mhp1, GlpT, EmrD, NhaA, and LacY, it was further possible to demonstrate an overall trend between protein stability and structural resolution. We suggest that by monitoring membrane protein stability with reference to the benchmarks described here, greater efforts can be placed on constructs and conditions more likely to yield high-resolution structures.